Produção e extração de exopolissacarídeos de cepas de lactobacillus spp. potencialmente probióticas - Bomfim, Vanessa Barbosa (2019)
Lactic acid bacteria (LAB) are excellent exopolysaccharides (EPS) producers, which has attracted the interest of the scientific community because they are produced by microorganisms that are generally recognized as safe (GRAS). The EPS produced by LAB have gained much importance due to their technological and health properties. In this study, the production of EPS by Lb. mucosae CNPC007, Lb. rhamnosus EM1107 and Lb. plantarum CNPC003 was investigated. In addition, the influence of commercial starter cultures, often used in fermented dairy products, on the growth capacity of these three Lactobacillus strains was verified. It was possible to observe by the microbial interaction analysis that there was no inhibition zones formation for any of the strains against the starter cultures used, as well as between the probiotic strains themselves, indicating that these microorganisms can be used together for the production of fermented dairy. The microorganisms were cultured for EPS production in MRS control medium (containing glucose) and in formulated and modified MRS medium replacing glucose with the addition of fructooligosaccharides (FOS), identified as MRSg and MRSf. Lactobacillus plantarum CNPC003 produced a higher amount of EPS, presenting higher yield (568.4 mg/L) in MRS medium added with FOS compared to MRS control medium, containing glucose (378 mg/L). Carbohydrate and protein content in EPS FOS was 36.95 ± 0.24% and 0.68 ± 0.08%, respectively, while EPS GLU showed 42.48 ± 0.04% carbohydrate and 0.87 ± 0.05% protein. Infrared spectroscopy analysis confirmed the polysaccharide structure of the two EPS of Lb. plantarum CNPC003, and thermal analysis demonstrated the good stability of these polymers under high temperatures and can withstand temperatures up to 210 °C, important property for possible industrial applications. Composition of monosaccharides and HSQC (Heteronuclear Single Quantum Coherence) analyzes showed that these EPS are heteropolysaccharides, mainly constituted of mannose and glucose, with small amounts of galactose. EPS samples also showed significant in vitro antioxidant capacity, especially EPS FOS, with ABTS radical scavenging activity of 90.88 ± 0.80% at a concentration of 8 mg/mL. These results confirm the possibility of its use as a natural antioxidant in the food industry.